2020
DOI: 10.1101/2020.12.17.423130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of miR-155 attenuates lung cytokine storm induced by SARS-CoV-2 infection in human ACE2-transgenic mice

Abstract: Coronavirus disease 2019 (COVID-19) is a recent global pandemic. It is a deadly human viral disease, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with a high rate of infection, morbidity and mortality. Therefore, there is a great urgency to develop new therapies to control, treat and prevent this disease. Endogenous microRNAs (miRNAs, miRs) of the viral host are key molecules in preventing viral entry and replication, and building an antiviral cellular defense. Here, we have anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Zhai et al [ 137 ] identified a Borna virus-encoded protein which is able to suppress the expression of miR-155, which is implicated in innate immune responses. The suppression of miR-155 showed to attenuate lung cytokine storm in mice infected with SARS-CoV-2 [ 138 , 139 ]; here, we suggest that miR-155 could be regulated by viral proteins as well. Along the same line, miR-146a, miR-21, and miR-142 were found in COVID-19 patients triggering the inflammatory machinery through activating MAPK and NF-Ƙb signaling [ 140 ].…”
Section: Ability Of Sars-cov-2 Escaping the Host Immune System Throug...mentioning
confidence: 73%
“…Zhai et al [ 137 ] identified a Borna virus-encoded protein which is able to suppress the expression of miR-155, which is implicated in innate immune responses. The suppression of miR-155 showed to attenuate lung cytokine storm in mice infected with SARS-CoV-2 [ 138 , 139 ]; here, we suggest that miR-155 could be regulated by viral proteins as well. Along the same line, miR-146a, miR-21, and miR-142 were found in COVID-19 patients triggering the inflammatory machinery through activating MAPK and NF-Ƙb signaling [ 140 ].…”
Section: Ability Of Sars-cov-2 Escaping the Host Immune System Throug...mentioning
confidence: 73%
“…In mammalian cells, miR-136 binds to the 3′-UTR of RIG-I transcript and promotes IL-6 and IFNβ accumulation. Likewise, the expression levels of IL-6 and IL-8 were significantly increased by miR-21-3p, miR-21-5p and miR-155-5p [11] , [58] , [59] . On the other hand, miR-146a, miR-146b and miR-200c reduce the expression of IL-6, IL-8, and C-C motif chemokine ligand 5 (CCL5) [60] , [61] .…”
Section: Targeting Immune Regulatory Mirnasmentioning
confidence: 91%
“…IL-1 is mostly secreted by activated macrophages, neutrophils, and epithelial cells, which enhance the production of T lymphocyte–derived cytokine and Th2 cell responses. miR-155 upregulates IL-1 signaling pathway, while in contrary miR-146a depletion leads to IL-1, IL-6 and TNFα overproduction [59] , [64] , [67] . Therefore, modulation of these miRNAs would be useful in the control of the immune response in severe COVID-19 patients.…”
Section: Targeting Immune Regulatory Mirnasmentioning
confidence: 99%
“…Transcriptome analysis of three different human cell lines infected with SARS-CoV2 showed induction of inflammation-linked miRNAs such as miR-155, which is correlated with several viral diseases and involved in pulmonary damage in ARDS [305]. Moreover, in SARS-CoV2-infected transgenic mice expressing human ACE2, anti-miR-155 downregulated expression of miR-155 and reduced levels of pro-inflammatory cytokines, and improved survival of experimental animals [306]. Li et al analyzed differential expression of miRs in blood of ten COVID-19 patients and four healthy controls and identified top ten upregulated miRNAs of which miR-16-2-3p was the most upregulated, and top ten downregulated miRNAs of which miR-627-5p was the most downregulated [307].…”
Section: Host Mirna and Sars-cov2 Replicationmentioning
confidence: 98%